Effectiveness of Using ArchiCAD in Interactive 3D Visualization in Building Drawing Engineering Learning Media - Dinur Syahputra; Cut Lika Mestika Sandy; T. Sukma Achriadi Sukiman; Ericky Benna Perolihin Manurung; Reyhan Achmad Rizal (Brilliance: Research of Artificial Intelligence, 2025)
This study aims to analyze the effectiveness of using ArchiCAD software as a tool for interactive 3D visualization in the context of learning media for building drawing engineering. Traditional methods of teaching technical drawing often rely on two-dimensional representations, which can limit students’ spatial understanding and comprehension of complex architectural forms. By integrating ArchiCAD, a Building Information Modeling (BIM)-based software, students are exposed to a more immersive and realistic learning experience, enabling them to visualize construction elements more clearly. The research employs a quasi-experimental method involving two groups: an experimental group using ArchiCAD-based interactive media and a control group using conventional methods. Data collection was conducted through pre-tests and post-tests, as well as student perception questionnaires. The results indicate a significant improvement in the learning outcomes of the experimental group, both in terms of cognitive understanding and design skills. Furthermore, student responses show a high level of satisfaction and engagement when using 3D interactive media. These findings suggest that ArchiCAD can be effectively implemented as a digital learning medium in vocational and technical education settings, especially in the field of architectural drawing. The study recommends broader integration of BIM-based tools to support competency-based learning and enhance the quality of engineering education.